Promoting university students' situational engagement in online learning for climate education - Vilhunen, Elisa; Vesterinen, Veli-Matti; Äijälä, Mikko; Salovaara, Janne; Siponen, Joula; Lavonen, Jari; Salmela-Aro, Katariina; Riuttanen, Laura (Elsevier BV, 2025)
Disengagement in online learning is known to pose a risk to student learning and wellbeing. In this paper, we first introduce the development and implementation process of a set of online university climate education courses aimed at enhancing student situational engagement through diverse learning activities. Second, engagement (conceptualized here as the co-occurrence of interest, skill, and challenge, i.e., optimal learning moments), and activities during the online courses were examined through ecological momentary assessment, and the relationship between them was investigated through two-level regression models. The results showed that the students were likely to experience optimal learning moments when they were formulating problems and ideating alternatives or designing solutions. Formulating problems and ideating alternatives can promote a student sense of competence, and by designing solutions, students can work with adequately challenging learning tasks. Thus, by implementing such activities in (online) teaching and learning, educators can contribute positively to student engagement.